Synthesis and characterizations of silver/polymethylmethacrylate nanocomposites via in-situ technique / Noorsaiyyidah Darman Singho - Noorsaiyyidah, Darman Singho (2013)
In the present study, the synthesis of Ag/PMMA nanocomposites is addressed. AgNO3 was used as a source of silver ions, polyethylene glycol (PEG) as a reducing agent and Daxad 19 as a stabilizer and reducing agent. Silver nanoparticles were synthesized by chemical reduction method in various concentration of silver nitrate (AgNO3) and Daxad 19 at different reactant temperature. The as-synthesized silver nanoparticles were used as primary source to produce Ag/PMMA nanocomposites via in-situ technique. The effect of reactant temperatures, PMMA weight ratio and the percentage loading of silver nanoparticles in the Ag/PMMA nanocomposites were studied. UV-vis studies indicate that the maximum surface plasmon resonance (SPR) peak occurred at 419 nm with refractive index, 1.8. The smallest particle size is 24 nm as shown from the TEM image. FESEM studies show that Ag/PMMA nanocomposites start to agglomerates at higher temperature, 120 °C. TGA studies indicate that the stability of Ag/PMMA nanocomposites increases when the percentage loading of silver nanoparticles in PMMA increases. FTIR studies show that the chemical bonding are dominated by AgNO3, PMMA and DMF solution. The Raman spectra of Ag/PMMA nanocomposites for 10 percent loading of silver nanoparticles get enhanced with increasing of reactant temperature. The dielectric studies indicate that the dielectric constant, ɛ’ and dielectric loss, ɛ” increase with the increase of percentage loading of silver nanoparticles in PMMA. The optimum result of the synthesis Ag/PMMA nanocomposites is at 80 °C with 10 percent loading of silver nanoparticles.